2011
DOI: 10.1088/0004-637x/731/1/34
|View full text |Cite
|
Sign up to set email alerts
|

The Allen Telescope Array Twenty-Centimeter Survey—a 700-Square-Degree, Multi-Epoch Radio Data Set. Ii. Individual Epoch Transient Statistics

Abstract: We present our second paper on the Allen Telescope Array Twenty-centimeter Survey (ATATS), a multi-epoch, ∼700 deg 2 radio image and catalog at 1.4 GHz. The survey is designed to detect rare, bright transients as well as to commission the ATA's wide-field survey capabilities. ATATS explores the challenges of multi-epoch transient and variable source surveys in the domain of dynamic range limits and changing (u, v) coverage. Here, we present images made using data from the individual epochs, as well as a revis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 13 publications
3
38
0
Order By: Relevance
“…The sources were detected in a drift scan mode and have flux densities greater than 1 Jy, with typical timescales of minutes to days. (Note, however, the questions raised about these results by Croft et al 2010Croft et al , 2011, and the discussion about the resulting transient event rates by Ofek et al 2011. ) As briefly discussed earlier in Section 3.1, Bower et al (2007) reported the detection of 10 transient radio sources in archival VLA data at 4.8 and 8.4 GHz.…”
Section: Gigahertz Surveysmentioning
confidence: 98%
See 1 more Smart Citation
“…The sources were detected in a drift scan mode and have flux densities greater than 1 Jy, with typical timescales of minutes to days. (Note, however, the questions raised about these results by Croft et al 2010Croft et al , 2011, and the discussion about the resulting transient event rates by Ofek et al 2011. ) As briefly discussed earlier in Section 3.1, Bower et al (2007) reported the detection of 10 transient radio sources in archival VLA data at 4.8 and 8.4 GHz.…”
Section: Gigahertz Surveysmentioning
confidence: 98%
“…They did not detect any transients, placing an upper limit of ρ < 0.004 deg −2 on the transient rate for sources with flux greater than 40 mJy at 1.4 GHz. Croft et al (2011) extended this analysis presenting results for an individual epoch-to-epoch comparison for the ATATS data set. They derived a limit of ρ < 6 × 10 −4 deg −2 for transients brighter than 350 mJy at 1.4 GHz.…”
Section: Gigahertz Surveysmentioning
confidence: 99%
“…As this is the first transient survey in the millimeter band, comparison of these results to previous surveys (e.g., Levinson et al 2002;Gal-Yam et al 2006;Bower et al 2010;Bell et al 2011;Bower & Saul 2011;Croft et al 2011) is a complex and model-dependent task. The highest frequency of these (Bower et al 2010) was conducted at 5 GHz, a factor of 30 below our primary observing band, and correspondingly was focused on somewhat different sources.…”
Section: Population Constraintsmentioning
confidence: 99%
“…Early blind searches for transient sources suggest that a bright (ࣙ0.1 Jy), frequent, population of GHz transients does not exist (see e.g. Croft et al 2010Croft et al , 2011Bower et al 2010;Bower & Saul 2011;Bell et al 2011). The benchmark survey of Bower et al (2007) which predicted a substantial number of radio transients in the sub-mJy range has recently been revised by Frail et al (2012), lowering the predicted surface density of sources.…”
Section: Variability and Transientsmentioning
confidence: 99%